Reformulation of the Epistemology of Islamic Education: Examine Noeng Muhadjir's Thoughts - Hamka (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
This article shows that revelation is a barometer of the truth of science, as can be concluded from Noeng Muhadjir's thoughts. Any scientific product cannot be accepted if it is in apparent contradiction with the qat'i nash. This article is classified as qualitative research that uses a library research model. The primary data source is the works of Noeng Muhadjir, especially the article entitled, "Epistemology of Islamic Education The Theoretical-Philosophical Approach", contained in the book Reformulation of Islamic Education Philosophy, and "Education in Perspective The Koran: A Micro Review”, contained in the book Education in the Perspective of the Koran. Other works are used as support. The method used in this paper is discourse analysis. The conclusion that can be drawn from the discussion results is that Noeng Muhajir takes the basis as an epistemological basis for Islamic education on the philosophy of metaphysical realism (popper) and phenomenology (ponty) as postulates of anthology and axiology. Noeng Muhadjir's ideas were driven by the spirit of bringing together science and revelation while maintaining the scientific characteristics of science and the absolute truth of revelation.